Restoration Effect Of Pharmacopuncture In Orsopathy Of Vertebrogenic Etiology In Highly Qualified Weightlifters (Texas Journal of Agriculture and Biological Sciences, 2023)
The article contains mainly theoretical material that allows substantiating the effect of pharmacopuncture on the regenerative processes of the cartilaginous tissue of human inter vertebral discs. The mechanism of starting the process of sanogenesis and its action (based on the theory of the existence and functioning of the bio electromagnetic homeostasis of the human body) in the restoration of damaged intervertebral discs by the pharmacopuncture method is considered